Pest trap and natural enemy nursery merged in Lobularia maritima? - Janique Koller; Lindsey Norgrove; Virginie Dekumbis; Dylan Maret; Louis Sutter (Arthropod-Plant Interactions, 2024)
Planting crops to push or pull pests from a main crop and floral enhancements to attract natural enemies are emerging as pivotal agroecological strategies to shift away from synthetic pesticides. The brassica, Lobularia maritima, has great potential to act as a floral enhancement as it is attractive to many insects and improves the fitness of and biocontrol services provided by multiple natural enemies. It has been mainly deployed as an insectary plant; few studies have been conducted on its use as a trap plant. We explored the potential of L. maritima as a targeted flower enhancement in sheltered cropping systems through three case studies: (1) as flower strips alongside a cucumber crop, (2) as flower strips alongside a strawberry crop in a replicated on-farm experiment, and (3) as hanging pots under strawberry cultivation gutters. We monitored beneficial and pest insects in flowers and crops and assessed crop damage. Lobularia maritima stands out as an excellent floral enhancement plant due to its ease of cultivation and its ability to flower consistently over an extended period. Generalist predatory bugs, such as Orius laevigatus and Macrolophus pygmaeus , had higher densities on L. maritima than on other flowers grown next to strawberries. We found more thrips on L. maritima and less thrips on crops in two out of three experiments, compared with controls. Further research is needed to confirm if L. maritima is an effective trap crop for thrips and other pests and to detect possible dis-services, such as the attraction of phytophagous bugs.